Evaluation of an Open Surgical Skills Curriculum. (October 2016) - Beasley, Anitra; Kilpatrick, Charles; Swift, Steven
Abstract : BACKGROUND: Work-hour limitations and focus on patient safety have necessitated changes to the traditional apprenticeship-based resident education model. This is especially true for surgical specialties where training opportunities must not only increase in efficiency but also shift to settings outside of the operating room. While validated curricula exist for laparoscopic skills, similar curricula for open skills are scare and not well validated across specialties. METHODS: The Southwestern Center for Minimally Invasive Surgery open knot-tying and suturing curriculum has been validated in a general surgery sample and consists of 11 standardized tasks using commercially available materials. The full curriculum includes an orientation, video tutorials, proctored baseline assessment, individual practice, and proctored post-testing. We tested elements of the curriculum through baseline assessment. RESULTS: Residents from all levels of our program attended orientation and rotated through the skills stations for baseline assessment. With minor exceptions, tasks were able to be performed as described. Baseline performance between intern and upper level trainees was significantly different for basic knot tying and suturing ( P <.05). DISCUSSION: We were able to provisionally implement a simple yet comprehensive curriculum for open knot-tying and suturing. The differential performance of upper and lower level residents demonstrates construct validity in our sample. We anticipate that skill acquisition will be demonstrated by a majority of trainees by completion of the entire curriculum.